2010
DOI: 10.1108/09596111011035927
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles and burnout: is there an association?

Abstract: Purpose -The primary purpose of this paper is to investigate the association between leadership styles and burnout among hospitality managers currently working in the industry of Cyprus. Specifically, transformational, transactional and passive/avoidance are to be investigated in order to establish which leadership style is more prone to burnout effects. Design/methodology/approach -Adopting a quantitative approach, the multifactor leadership questionnaire (MLQ 5X-Short) was utilized to allow research particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 65 publications
5
45
0
1
Order By: Relevance
“…Its purpose was to empirically examine the effect of three leadership styles, namely transformational, transactional and laissez-faire leadership, on job-relatedstress presenteeism in knowledge workers across a number of industries in South Africa. Although leadership has been extensively researched, it remains difficult to understand the full extent of the complex interrelationships involved in leadership processes (Zopiatis & Constanti, 2010). Leadership style is of particular interest to researchers (Ogbonna & Harris, 2000) as it impacts both employee and organisational performance.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations
“…Its purpose was to empirically examine the effect of three leadership styles, namely transformational, transactional and laissez-faire leadership, on job-relatedstress presenteeism in knowledge workers across a number of industries in South Africa. Although leadership has been extensively researched, it remains difficult to understand the full extent of the complex interrelationships involved in leadership processes (Zopiatis & Constanti, 2010). Leadership style is of particular interest to researchers (Ogbonna & Harris, 2000) as it impacts both employee and organisational performance.…”
Section: Purposementioning
confidence: 99%
“…Laissez-faire leaders tend to avoid any involvement with their subordinates. Numerous researchers have investigated the relationship between these leadership behaviours and various phenomena, such as burnout, stress, job satisfaction and performance (Dale & Fox, 2008;Danish & Usman, 2010;Failla & Stichler, 2008;Yang, Huang & Wu, 2011;Zopiatis & Constanti, 2010). Hetland, Sandal and Johnsen (2007) studied the effects of leadership style on burnout in a Norwegian information technology firm and concluded that each style impacted the level of employee burnout differently.…”
Section: Leadership Stylementioning
confidence: 99%
See 1 more Smart Citation
“…The majority of leadership styles is evaluated unambiguously in the context of occupational burnout. Transformational, authentic, participative, or supportive leadership styles are related to lower probability of occupational burnout while transactional and laissez-faire leadership styles are related to higher probability of occupational burnout (Yuan, & Lee, 2011;Gill, Flaschner, & Shachar, 2006;Russell, 2014;Laschinger, Wong, & Grau, 2012;Zehir, Ertosun, Zehir, & Müceldili, 2011;Zopiatis, & Constanti, 2010;Kanste et al, 2007). Still the relationship between ethical leadership and burnout is not clear.…”
Section: Introductionmentioning
confidence: 95%
“…There are studies examining the relationship between leadership and various variables, such as organizational culture (Karadağ, 2009;Koşar & Çalık, 2011, Turan & Bektaş, 2013, organizational climate (Şentürk & Sağnak, 2012), performance (Özmen, 2005), job satisfaction (Yılmaz & Ceylan, 2011), organizational commitment (Buluç, 2009), burnout (Cerit, 2008) in the sample of overall Turkey. Also in the international literature it is possible to find many researchers testing the relationship between leadership and different organizational variables (Griffith, 2004;Khasawneh, 2001;Lok & Crawford, 2004;Zopiatis & Constanti, 2010).…”
mentioning
confidence: 99%